Plan de negocios para la creación de una empresa importadora de joyería desde China (2019)
Business plan for the creation of a jewelry importing company from China, the process was carried out taking into account the general fundamentals which allowed the import process on jewelry to be further developed. When developing the market study, it was satisfactory to obtain the result of the product to be imported since it does not have such an exclusive objective but rather has a wide reception and therefore is a viable project.